Multimodal Imaging Approach to MEN-1 Syndrome-Associated Tumors - Alice Carli; Elisa Boffa; Matteo Bonatti; Marco Chincarini; Maria Vittoria Davì; Giulia A. Zamboni (Diagnostics)
Multiple endocrine neoplasia type 1 (MEN-1) is an autosomal dominant inherited syndrome characterized by a genetic predisposition for the development of specific hormone-secreting tumors. Effective diagnosis and management of MEN-1 require genetic testing, regular surveillance, and imaging follow-up to detect and monitor tumor growth or recurrence and to plan for surgical intervention. The aim of this narrative review is to provide an overview of the current imaging modalities and their role in the diagnosis and follow-up of patients affected by MEN-1, focusing on the detection and characterization of associated neoplasms. The knowledge of the most frequent MEN-1 associated neoplasms and their imaging features is crucial for an accurate diagnosis, management, and treatment.